Developing innovative ideas from citizens: A transactive memory perspective - Fernández Del Carpio, Alvaro (2015)
Citizens can be considered as an important source of knowledge for innovating in open contexts, collaborating with initiatives for developing solutions to urban issues, in order to get improvements addressed to a collective well-being. This paper presents an approach to including transactive memory aspects into the development of collective initiatives, as a vehicle of supporting the relationships between the memory systems of contributors of ideas. Providing a visual representation of elements and mechanisms for building ideas from citizen initiatives would make the collective interactions of creating, refining and maturing solutions more understandable. Through a case study, the visual schematization was designed and validated by a community comprised of members of universities, experts and some local citizens. Finally, the analysis of results disclosed encouraging appreciations of the participants in respect of this proposal. For many of them, it is a good instrument for communicating and transferring initiatives for building innovative solutions.